The Influence Of The Inquiry Learning Model On Student Learning Outcomes - Sihaloho, Binner (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This research aims to analyze: the differences in the influence of the inquiry learning model and the Direct Learning model on student learning outcomes; This research is quantitative research with a quasi-experimental design type. The population in this study was all class VIII of SMP Negeri 27 Medan for the 2022/2023 academic year. The test was carried out using Two Way ANOVA. The results of the research show that (1) there are differences in the influence between the inquiry learning model and the direct learning model on social studies student learning outcomes; There is no interaction between initial social studies abilities (high, medium and low) and learning models on student learning outcomes at SMP Negeri 4 Medan.